2013
DOI: 10.3109/00207454.2013.833198
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple sclerosis in the Levant: a regional consensus statement

Abstract: The epidemiology of multiple sclerosis (MS) is rapidly changing in many parts of the world. In a geographic area that was previously associated with low prevalence, recent studies showing high prevalence and fast rising incidence of MS in the Levant countries led us neurologists of this region to meet in a consensus panel, in order to share our latest findings in terms of MS epidemiology and consent on MS management in the Levant. Twelve neurologists and MS experts representing various countries of the Levant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The prevalence of MS among the Jewish Israeli population who originated in Iraq is relatively low, similarly to the prevalence of MS in non-Jewish Iraqi population and the low MS prevalence is in Middle Eastern countries as compared to Northern Europe [ 9 , 10 ]. Despite the low prevalence for MS, we noticed in our day-to-day clinical work, that Jewish relapsing-remitting MS patients who originated in Iraq progress fast to disability.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MS among the Jewish Israeli population who originated in Iraq is relatively low, similarly to the prevalence of MS in non-Jewish Iraqi population and the low MS prevalence is in Middle Eastern countries as compared to Northern Europe [ 9 , 10 ]. Despite the low prevalence for MS, we noticed in our day-to-day clinical work, that Jewish relapsing-remitting MS patients who originated in Iraq progress fast to disability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Atlas of MS compiled by the Multiple Sclerosis International Federation and the World Health Organization [ 5 ], the Arabian Gulf, which is geographically defined as part of the Western Asia region, is a low-risk zone for MS. This low-risk status remains despite the recent affluence and rising tide of ‘diseases of affluence’ [ 6 ] including MS [ 7 9 ] in the region. However, there are emerging epidemiological surveys which are challenging this low risk hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord involvement is the most common clinical manifestations of MS. 147 Compared to other continents, the advantage of the frequency of TM over that of visual disorders in Asia seems to be no significant. 142 , 148 151 A study comparing clinical characteristics between the Middle East and North Africa patients and Indian patients versus patients with European descent showed the frequency of spinal cord symptoms was not different between these groups. 151 A survey enrolled 142 MS patients in Pakistan showed that the most common initial symptoms were motor weakness (70%), followed by sensory symptoms (45%), while only 15% had bladder dysfunction.…”
Section: Clinical Featuresmentioning
confidence: 99%